2012
DOI: 10.3109/09513590.2012.730570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and body mass on the intensity of menopausal symptoms in 5968 Brazilian women

Abstract: Our results suggested that the age of menopause and BMI may influence the intensity of vasomotor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
5
16
1
1
Order By: Relevance
“…Also, hot flushes were not associated with menopause in the present study, while vasomotor symptoms were shown to be associated with BMI and age of menopause (23). This could be due to the retrospective data collection from medical records (database) that might have caused bias, as they were recorded based on patients' statement and not based on examination.…”
Section: Discussioncontrasting
confidence: 54%
“…Also, hot flushes were not associated with menopause in the present study, while vasomotor symptoms were shown to be associated with BMI and age of menopause (23). This could be due to the retrospective data collection from medical records (database) that might have caused bias, as they were recorded based on patients' statement and not based on examination.…”
Section: Discussioncontrasting
confidence: 54%
“…A separate study sample (N = 158,292) was drawn from the BOLD for patients who met the following inclusion criteria: (Flegal et al, 2012) women aged 40 to 65 years on the day of bariatric surgery, (Wang et al, 2011) patients who received RYGB, sleeve gastrectomy, or gastric banding procedure for the first time (to avoid confounding due to multiple bariatric procedures given to a single patient), (Davis et al, 2012) pre-operative BMI ≥ 30 kg/m 2 , (Royer et al, 2007) 100 cm ≤ pre- and post-operative height ≤ 210 cm (to minimize confounding due to extreme height), (Da Fonseca et al, 2013) 50 kg ≤ pre- and post-operative mass ≤ 400 kg (to minimize confounding due to extreme mass), (Karmali et al, 2013) z-score of % TWL < 3.3 (to minimize undue influence of outliers), and (Buchwald, 2005) 1 week ≤ follow-up period ≤ 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…A study found in Latin American women that the menopause increased the risk of metabolic syndrome and abdominal obesity as much as by 18% (Royer et al, 2007) A decline in ovarian hormone among middle-aged women can generate metabolic changes and other symptoms that help gain weight (Davis et al, 2012, Royer et al, 2007). It has been reported that women with a higher body mass index (BMI) are more likely to experience vasomotor symptoms, which is one of the important features of climacteric disturbance (Da Fonseca et al, 2013). This warrants an effective weight-reduction intervention for middle-aged women.…”
Section: Introductionmentioning
confidence: 99%
“…The role of hypoestrogenism in weight gain is unclear, but it is known that oestrogen deficiency contributes to the accumulation of abdominal fat, which increases the risk of metabolic disorders [1]. In our study, the early and late post-menopausal women were overweight and had high AC measurements, and after nutritional counselling, there was improvement in metabolic and cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 50%
“…The intensity of the menopausal symptoms manifests to a greater or lesser degree depending on the hormonal stage, ethnicity and lifestyle of the woman in addition to various cultural and psychosocial factors [1,2]. Myo-articular changes are observed in late post-menopausal women and muscle joint pain are predominant symptoms in post-menopause, while vasomotor symptoms are more common in early postmenopausal women [2,3].…”
Section: Introductionmentioning
confidence: 99%